Spectroscopic Characteristics of Dual - Color CdSe/CdS/CdSe1-xSx/CdS Quantum Dot - Quantum Wells - Anh Thi, Le; Dieu Linh, Nguyen; Duc Huy, Le; Thi Thuy Lieu, Nguyen; Thi Minh Hien, Nguyen; Xuan Nghia, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 38 No 4DO - 10.25073/2588-1124/vnumap.4769, 2022)
In this work, preparation and spectroscopic characteristics of CdSe/CdS/CdSe 1-x S x /CdS core/shell 1/well/shell 2 structure were presented. The obtained quantum dot - quantum well (QDQW) samples exhibited two emission peaks at 1.97 and 2.2 eV. Excitation power dependent photoluminescence (PL) of the QDQWs indicated that the integrated emission intensities of these peaks increase linearly with excitation power densities up to 1.3×10 2 mW/cm 2 . The temperature dependence of the bandgap energies of the QDQW’s core and well layer was well described using the Varshni expression. Evidence of the existence of “local wells” in the QDQW’s well layer that leads to a more significant change in the maximum position and full width at half maximum of the well’s emission peak compared to the core’s counterpart was discovered. Annealing samples resulted in the considerable increase of the well layer’s emission efficiency. Keywords: Quantum dot - quantum wells, dual - color, spectroscopic characteristics.